(untitled) (Revista Latino-Americana de Enfermagem, 1998)
The invasion of patient's territorial and personal space and its effects have been object of several international studies. In view of its importance and searching for an instrument of measure to develop research in this area, the present study aimed at adapting the instrument "anxiety due to territory and space intrusion questionnaire" to the brazilian culture. Authors fully described the phases of this process and utilized the software SPSS for the psychometric analysis.